ERA OF NEW TECHNOLOGIES FOR BRIDGES CONSTRUCTIONS - Klyuchnyk, S. V. (Science and Transport Progress, 2010)
In this paper the possibilities of protection of bridge structures from corrosion by thermal spraying of aluminum or zinc, which provides the long-term protection (approximately 50 years), are presented.